2008
DOI: 10.1080/09593330802270715
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preparation and Experimental Conditions on Removal of Phenol by Surfactant‐modified Zeolites

Abstract: The removal of phenol from aqueous solutions using surfactant-modified clinoptilolite-rich tuffs (SMZ) prepared from two Mexican zeolitic tuffs (Chihuahua and Oaxaca) was investigated. Sodium homoionization of the zeolitic rocks was performed before they were modified with the surfactants: hexadecyltrimethylammonium chloride or bromide and bencylcetildimethylammonium chloride. The surfactants in the modified zeolitic materials were determined considering the total carbon in the samples. The phenol removal was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The PSO model is arguably the most widely used kinetics sorption model and was used in the studies by Blandhard 1984, Ho andMcKay (1998b) and Chowdhury and Das (2011). It is often recommended because it considers system heterogeneity (Diaz-Nava et al 2008). The nonlinear (preferred) form of the PSO equation is:…”
Section: Model Backgroundmentioning
confidence: 99%
“…The PSO model is arguably the most widely used kinetics sorption model and was used in the studies by Blandhard 1984, Ho andMcKay (1998b) and Chowdhury and Das (2011). It is often recommended because it considers system heterogeneity (Diaz-Nava et al 2008). The nonlinear (preferred) form of the PSO equation is:…”
Section: Model Backgroundmentioning
confidence: 99%
“…In a previous work [10] was investigated the kinetic of the phenol adsorption by the SMZ used in the present work and it was found that phenol adsorption by the surfactant-modified zeolites reached the equilibrium in approximately 3 h and the equilibrium was main- tained until the final experimental time (72 h). It was also found that phenol adsorption data was best adjusted to kinetic model of pseudo-second order.…”
Section: Isothermsmentioning
confidence: 98%
“…In a previous work Díaz-Nava et al [10] determinated the kinetic parameters in order to know the phenol sorption behavior using surfactant-modified natural zeolites considering the preparation conditions of the SMZ, the type of surfactants which were used to modify the characteristics of the zeolitic surface, the source of the zeolitic material, the pH of phenol solutions as well as the concentration of phenol in the solutions in batch system. It was found that the sorption equilibrium on SMZ for phenol was reached in 24 h. Therefore in this paper the experimental conditions to obtain the isotherm curves were chosen according to the kinetic results.…”
Section: Phenol Sorption Isothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic compounds are important raw materials for fine chemicals and have been widely used in the fields of pharmaceuticals, feeds, resins, dyes, pesticides, and so forth . These phenolic compounds are highly toxic by ingestion or inhalation at the low concentrations . Nitrophenol and its isomers, which have been widely used in the production of pesticides, insecticides, and herbicides, have caused great harm to the environment and humans.…”
Section: Introductionmentioning
confidence: 99%